Efficacy of Melatonin Administration Via Different Route on Reproductive Performance and Blood Mineral Profile in Chhotanagpuri Ewe - Choudhary, Pankaj K.; Ishwar, Ajay K.; Kumar, Pramod; Kumar, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study aimed to evaluate the comparative efficacy of melatonin administration via different routes on reproductive performance and blood mineral profile of Chhotanagpuri ewe. A total of forty-two non-pregnant, non-lactating healthy ewes, not exposed to rams for 2 months, were allocated to seven equal groups each of six animals, viz., G1 (Normal day light control), G2 (Long day control, 16-18 h light; sunlight + artificial light), G3 (Long day as G2 + 3 mg melatonin daily orally), G4 (long day as G2 + 1 mg melatonin daily subcutaneous), G5 (Short day control, 8 hours sun light, rest darkness), G6 (short day as G5 + 3 mg melatonin daily orally), and G7 (short day as G5 + 1 mg melatonin daily subcutaneous). The melatonin treatment was given for one month to ewes of G3, G4, G6 and G7 and then were exposed to ram for one month, i.e., from day 61st to 90th; whereas the ewes of normal, long day and short day control (G1, G2, G5) were exposed to ram for one month from day 31st to 60th. Blood samples were collected from each animal, day before the start of experiment (day 0) and thereafter, every 30 days for five occasions. The estrus induction response was cent per cent in oral melatonin treated ewes (G3 and G6) compared to subcutaneous route (83.33%, G4 and 66.66%, G7) and controls (33.3 to 50.0%). After melatonin treatment, the overall estrus induction response and subsequent lambing rate were improved. The serum calcium level was significantly (p<0.05) lower in late pregnancy in G1 and G6; the serum phosphorus level was significantly (p<0.05) low in late pregnancy in all groups, except G5; the serum copper level was significantly lower in G6 compared to day 0 value. Furthermore, magnesium and zinc levels did not differ significantly within the treatment groups. In conclusion, the melatonin treatment can be used to improve reproductive performance of Chhotanagpuri ewe.